HIV, wages, and the skill premium - Ioana E. Marinescu (Institute for the Study of Labor (IZA), 2012)
The HIV epidemic has dramatically decreased labor supply among prime-age adults in sub-Saharan Africa. Using within-country variation in regional HIV prevalence and a synthetic panel, I find that HIV significantly increases the capital-labor ratio in urban manufacturing firms. The impact of HIV on average wages is positive but imprecisely estimated. In contrast, HIV has a large positive impact on the skill premium. The impact of HIV on the wages of low skilled workers is insignificantly different from 0, and is strongly dampened by competition from rural migrants. The HIV epidemic disproportionately increases the incomes of high-skilled survivors, thus increasing inequality.
urn:nbn:de:101:1-201207126181
Keywords: J22; I15; J31; 330; labor supply; wages; health; AIDS; HIV; development; AIDS; Arbeitsangebot; Lohnstruktur; Qualifikation; Bildungsertrag; Schätzung; Afrika südlich der Sahara